ASSESSMENT OF THE QUALITY OF HIGHER EDUCATION IN THE MANAGEMENT OF PERSONNEL POTENTIAL IN THE REGION - L. Shirokova; L. Kilimova (Вестник Северо-Кавказского федерального университета)
The study was conducted with the aim of assessing satisfaction with the quality of higher education received and assessing the state of the labor market in the region in order to identify directions for managing the balanced development of local labor markets and higher education at the regional level. In order to achieve this goal, the following tasks have been solved: collecting (by conducting a sociological survey), systematizing, statistically processing and analyzing information on the satisfaction of graduates of the educational organization of higher education with the quality of the received education and the possibility of professional self-realization in the regional labor market; identifying actions to improve the quality of education and priorities of the strategy, policy and goals of the educational organization; substantiation of the systemic role of the region itself in providing the regional economy with highly skilled personnel. As a result, the high satisfaction of university graduates with their professional activities in the direction of training and interest in continuing contacts with the educational organization, including to continue the personal educational trajectory, was established. At the same time, the low satisfaction of graduates with the level of wages received, the prospects for professional development in the region indicate systemic problems in the social and economic spheres of the region, imbalances in regional labor markets and higher education, and the inefficiency of HR strategies applied by regional employers. The growth of the region's personnel potential, the provision of a regional economy with highly qualified personnel is possible as a resu mar lt of systematic uninterrupted work on the basis of mutual adaptation of agents of the higher education et and the labor market.